Karakterisasi kulit kayu tingi (Ceriops tagal) sebagai bahan penyamak nabati - Emiliana Kasmudjiastuti (Majalah Kulit, Karet, dan Plastik, 2014)
Tingi (Ceriops tagal) bark was highly potential as tanning materials due to high tannin concentration. The aim of the study was to determine the characterization of properties of tanning material made from tingi bark, including the tannin levels, the non-tannin levels, the tannin type, the absorption level of the solution and the FTIR spectrum analysis. The method used in this research was countercurrent system in the extraction process, feed solution preparation process, the thickening process, powder formation process conducted with the aid of Rotavapor- 151 Standard, and testing. The results showed that the tingi bark contains tannin level 70.91% and non-tannin levels 10.63%. Tannins from tingi bark were classified as procyanidin condensed tannins type and the absorption values obtained maximum value at wavelength 490 nm. The FTIR spectral data indicated that tingi tannins contained hydroxyl group (ⱱ O-H; ⱱ N-H) in the area (3467.418-3057.025) cm-1, aromatic group (ⱱ C-H) in the area of 2875,733 cm-1, ⱱ C=O (ester group in tanned material) in the area (1747.442-1612.422) cm-1, ⱱ-OH; R-COO-in the area of 1444.626 cm-1 and ⱱ(SO4)2 -; R-SO3; R-SO3H in the area (1112.823-1062.729) cm-1. Keywords: FTIR spectrum, procyanidin, tingi bark, tannin, solution absorption ABSTRAKKulit kayu tingi (Ceriops tagal) berpotensi sebagai bahan penyamak nabati mengingat kandungan tanin yang tinggi. Tujuan penelitian adalah untuk mengetahui karakterisasi bahan penyamak tingi terhadap kadar tanin, kadar non tanin, tipe tanin, absorpsi larutan tingi dan spektrum FTIR. Metode yang dilakukan meliputi pembuatan ekstrak larutan dengan sistem counter current, preparasi larutan umpan, pemekatan, pembentukan serbuk menggunakan Rotavapor-151 Standard, dan pengujian. Hasil karakterisasi kulit kayu tingi menunjukkan kandungan tanin 70,91% dan kadar non tanin 10,63%. Tanin tingi termasuk golongan condensed tannin tipe procyanidin dan absorpsi larutan tingi didapatkan panjang gelombang maksimum 490 nm. Data spektrum FTIR tanin tingi menunjukkan adanya gugus hydroksil (ⱱO-H; ⱱN-H) pada area (3467,418-3057,025) cm-1, gugus aromatik (ⱱC-H) pada area 2875,733 cm-1, ⱱC=O (ester group in tanned material) pada area (1747,442-1612,422) cm-1, ⱱ-OH; R-COO- pada area 1444,626 cm-1 dan ⱱ(SO4)2-; R-SO3; R-SO3H pada area (1112,823-1062,729) cm-1.Kata kunci: spektrum FTIR, procyanidin, kulit kayu tingi, tanin, absorpsi larutan.